The Integration of Biology Into the Treatment of Diffuse Intrinsic Pontine Glioma: A Review of the North American Clinical Trial Perspective - Clymer, Jessica; Kieran, Mark W. (Frontiers in Oncology, 2018)
Dramatic advances in the molecular analysis of diffuse intrinsic pontine glioma have occurred over the last decade and resulted in the identification of potential therapeutic targets. In spite of these advances, no significant improvement in the outcome has been achieved and median survival remains approximately 10 months. An understanding of the approaches that have been taken to date, why they failed, and how that information can lead the field forward is critical if we are to change the status quo. In this review, we will discuss the clinical trial landscape in North America with an overview of historical approaches that failed and what might account for this failure. We will then provide a discussion of how our understanding of the genotype of this disease has led to the development of a number of trials targeting the mutations and epigenome of DIPG and the issues related to these trials. Similarly, the introduction of methodologies to address penetration across the blood brain barrier will be considered in the context of both targeted approaches, epigenetic modification and immune surveillance of these tumors. The comprehensive analysis of this data, generated through cooperative groups, collaborative clinical trials and pilot studies in North America will be the focus of the IVth Memorial Alicia Pueyo international symposium in Barcelona on March 12th, 2018 and will be compared and contrasted with a similar comprehensive analysis of the European data with the goal of bringing all of this data together to develop a uniform platform on which new rational trials can be based.